Comparison of Depression Rates Between Students Living with Parents and Living Alone in Unpri Medical Students Class of 2022 - Nst, Bulan Ramadhani; Adhayani, Adhayani; Natali, Oliviti (CV. Publikasi Indonesia, 2025)
Depression is one of the most common mental health disorders among university students, especially medical students who face high academic demands and psychological pressure throughout their education. According to the World Health Organization (WHO, 2021), more than 264 million people worldwide experience depression, with a rising trend among young adults, including students. Living arrangements are believed to influence depression levels, as students living independently tend to have lower emotional and social support compared to those living with their parents. This difference in social environment may affect the mental well-being of medical students. This study aimed to compare the depression levels between medical students living with their parents and those living independently at the Faculty of Medicine, Universitas Prima Indonesia (UNPRI), class of 2022. This research used a descriptive comparative design with a quantitative approach. The sample consisted of 67 respondents selected using purposive sampling. Data were collected using the Beck Depression Inventory-II (BDI-II) questionnaire and analyzed with the Independent Sample T-Test at a 0.05 significance level. The findings showed a significant difference in depression levels between students living with their parents and those living independently (p = 0.003). Students living with their parents had lower depression scores compared to those living independently. There is a significant difference in depression levels between medical students living with their parents and those living independently. Family social support plays an important protective role in reducing the risk of depression among medical students.